2022
DOI: 10.1038/s41467-021-27896-z
|View full text |Cite
|
Sign up to set email alerts
|

Matrix mechanics regulates epithelial defence against cancer by tuning dynamic localization of filamin

Abstract: In epithelia, normal cells recognize and extrude out newly emerged transformed cells by competition. This process is the most fundamental epithelial defence against cancer, whose occasional failure promotes oncogenesis. However, little is known about what factors determine the success or failure of this defence. Here we report that mechanical stiffening of extracellular matrix attenuates the epithelial defence against HRasV12-transformed cells. Using photoconversion labelling, protein tracking, and loss-of-fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 59 publications
2
30
1
Order By: Relevance
“…However, to our knowledge very few studies so far have explicitly tried to address the role of ECM stiffness in regulating any type of cell competition. Pothapragada et al recently found that stiffening of the ECM attenuates extrusion of oncogenically transformed MDCK cells driven by their wild-type neighbors, which is the opposite of what we find in the case of infection ( Pothapragada et al, 2022 ). In this study, however, which involves only two cell populations, cellular biomechanics were not characterized and the reasoning behind the enhanced elimination observed on soft ECM was the dynamic localization of the actin crosslinking protein filamin.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge very few studies so far have explicitly tried to address the role of ECM stiffness in regulating any type of cell competition. Pothapragada et al recently found that stiffening of the ECM attenuates extrusion of oncogenically transformed MDCK cells driven by their wild-type neighbors, which is the opposite of what we find in the case of infection ( Pothapragada et al, 2022 ). In this study, however, which involves only two cell populations, cellular biomechanics were not characterized and the reasoning behind the enhanced elimination observed on soft ECM was the dynamic localization of the actin crosslinking protein filamin.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, Gradeci et al, showed that changes in the ratio of winner-to-loser cell stiffness altered the kinetics of cell competition between wild-type MDCK cells and cells depleted for the polarity protein scribble, although ECM stiffness was not addressed in this study ( Gradeci et al, 2021 ). Another study on competition between wild-type cells and oncogenically-transformed ones did show that increasing ECM stiffness attenuates extrusion of transformed cells by tuning the dynamic localization of filamin, an important F-actin crosslinking protein ( Pothapragada et al, 2022 ). Thus, it remains unclear whether there are generalizable mechanisms that could predict how ECM stiffness impacts cell behavior and thus the outcome of a cell competition, and whether those would apply to epithelial cells that are infected with intracellular bacterial pathogens, which can replicate intracellularly and also dynamically spread from cell to cell.…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion of transformed cells is an epithelial defense mechanism against cancer that involves increased lateral interfacial actomyosin contractility [37] (Figure 2). However, cancer-induced stiffening of the surrounding ECM drives reorganization of the cytoskeleton of healthy cells including perinuclear localization of filamin that impedes extrusion [38].…”
Section: Trends In Cancermentioning
confidence: 99%
“…Active responses of the stromal niche surrounding the mutant cells, including a mesenchymal activation or a change in the composition of the extracellular matrix, may influence the expansion of certain clones and favor the clearance of others. For instance, increased mechanical stiffening of the extracellular matrix is thought to attenuate the extrusion of mutant cells from the epithelium 83 .…”
Section: Somatic Mutations and Cancer Transformationmentioning
confidence: 99%